2018
DOI: 10.1016/j.contraception.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Two-year contraceptive continuation rates among immediate postpartum implant users at a district hospital in Malawi: a prospective cohort study

Abstract: ObjectiveTo compare 2-year continuation rates in Malawian women undergoing immediate postpartum insertion of the levonorgestrel implant or etonorgestrel implant.Study designWe followed 159 women who underwent immediate postpartum levonorgestrel implant or etonorgestrel implant insertion at Kasungu District Hospital for up to 2 years.ResultsWe analyzed continuation data on 145 (92.4%) implant users. The 2-year continuation rates were 93.4 (95% CI 86.5–96.8) for levonorgestrel implant and 96.3 (95% CI: 76.5–99.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(12 reference statements)
1
1
0
Order By: Relevance
“…In this study, we found that the immediate postpartum jadelle implantation continuation was 145 (92.40%) at the end of 2 years, which is comparable to studies in other developing countries 3 , 4 as well as LARC continuation rates are higher than for other methods. 3 - 5 - 6 In Nepal the studies regarding the continuity of immediate post-partum Jadelle implant use are limited.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, we found that the immediate postpartum jadelle implantation continuation was 145 (92.40%) at the end of 2 years, which is comparable to studies in other developing countries 3 , 4 as well as LARC continuation rates are higher than for other methods. 3 - 5 - 6 In Nepal the studies regarding the continuity of immediate post-partum Jadelle implant use are limited.…”
Section: Discussionsupporting
confidence: 86%
“…The study on immediate postpartum implant users in Malawi found that the continuation rates of both levonorgestrel and etonorgestrel implants were high at 2 years, regardless of the method of delivery. 4 However in another study done in Tanzania, observed that the women delivered by cesarean section had higher continuation rate for LARC when compared to normal vaginal delivery. 12 In the present study, primi-para woman was 45.51%, followed by the woman with second parity (41.37%), who gave continuity to jadelle implant till two years.…”
Section: Discussionmentioning
confidence: 93%